Obtenção do pó da polpa de cajá-manga (Spondias dulcis) por diferentes métodos de secagem - Lara Junior, Jovan Marques (2021)
The main objective of this work was to obtain powdered cajá-mango pulp by spray drying, lyophilization and fluidized bed processes, in addition to evaluating its physical and physicochemical characteristics. The physical-chemical characterization of the whole pulp of cajá-manga and the powders obtained was carried out, in addition to the determination of the best condition of drying by spray-dryer, lyophilization and fluidized bed and concentration of the adjuvant (maltodextrin) through a composite design. rotational center 22. The physicochemical stability of the powders obtained in different packages for 90 days was also verified. The hygroscopic behavior, morphology and rheological characteristics of the powders obtained were evaluated. It was not possible to obtain an optimal point in the drying of cajá-manga pulp by the evaluated drying processes. The humidity, water activities, solubility and hygroscopicity of the powders obtained showed compatible and favorable values for the maintenance of the quality of dehydrated products. The laminated packages showed superior results in the study of physicochemical stability, which showed an increase in moisture and water activity, reduction in titratable acidity and remained stable in hygroscopicity and solubility after the evaluation time. The BET, BET and GAB models were the ones that best represented the sorption isotherms for the cajá-manga powders obtained by the spray-dryer spray drying, lyophilization and fluidized bed processes, respectively. The lyophilized powder presented irregular geometric shapes and great variation in size, while the powders obtained in spray-dryer and fluidized bed presented particles with rounded shape, with smaller size distribution and less segregation. The cajá-manga powders showed differences between the compaction densities and the apparent densities, greater for the powders that were obtained with higher maltodextrin concentration. The increment of maltodextrin with a drying adjuvant agent resulted in a decrease in the resistance to flow of cajá-manga powders. The drying processes were efficient in the drying of cajá-manga pulp using maltodextrin as a drying adjuvant and the powders were stable for 90 days.